Implementation Of Public Accountant Professional Standards (SPAP) Through Excel-Based Atlas Audit Application At Public Accounting Firms - Hanna Nurul Fadilah; Bambang Setyobudi Irianto; Siti Maghfiroh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of digitalization in the era of technology and information has brought changes in the implementation of audit procedures in Public Accounting Firms. The application of audit technology is not only aimed at improving the efficiency of auditors' work, but also to ensure compliance with the Public Accounting Professional Standards (SPAP). This study aims to analyze the implementation of SPAP through the use of Excel-based ATLAS audit applications in the financial statement audit process. The research method used is qualitative descriptive with data collection techniques in the form of theoretical studies, field observations, and analysis of audit working paper documentation. The results of the study show that the ATLAS application not only makes it easier for auditors to compile and document audit working papers, but also helps ensure that each stage of the audit is in accordance with the applicable SPAP provisions in Indonesia. The use of ATLAS not only improves the efficiency and accuracy of the audit process, but also supports the improvement of the overall quality of audit results. Thus, it can be concluded that the Excel-based ATLAS audit application plays an important role as a supporting tool in the implementation of SPAP and in improving the quality of auditing financial statements at Public Accounting Firms.